MENGANALISIS KINERJA KEUANGAN PT UNILEVER INDONESIA, TBK PERIODE 2021-2024 MENGGUNAKAN RATIO KEUANGAN - Matruty, Dinatonia Jovery (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
PT. Unilever Indonesia, Tbk is part of Unilever Global which has been operating in Indonesia for more than 1 (one). This company produces and markets products that are needed every day. Business challenges are getting bigger for Unilever in this digital era because many similar products are present. This writing is intended to find out the financial performance of PT. Unilever Indonesia, Tbk in 2021-2024. The analysis of the company's financial performance was carried out using financial ratio analysis, by utilizing balance sheet data and the company's income statement in the same year. The results of the analysis show that the financial performance of PT Unilever Indonesia, Tbk in 2021-2024 was not good in terms of liquidity ratio, leverage, efficiency, profitability ratio and market ratio. This condition is a sign for management to pay more attention to production so that it is not excessive in the warehouse, and the sales strategy must be managed again, so that the resulting profit can be maximized and at the same time become a magnet for new investors to invest in the company. The company must be selective in using debt and the financial structure must be considered. It is important for company management to pay attention to the company's financial performance because this will provide a comprehensive picture of the company's performance. ABSTRAK PT. Unilever Indonesia, Tbk bagian dari Unilever Global yang telah beroperasi di Indonesia lebih dari 1 (satu). Perusahaan ini memproduksi sekaligus memasarkan produk-produk yang dibutuhkan sehari-hari. Tantangan bisnis semakin besar bagi Unilever di era digital ini karena banyak produk-produk sejenis yang hadir. Penulisan ini dimaksudkan untuk mengetahu kinerja keuangan PT. Unilever Indonesia, Tbk tahun 2021-2024. Analisis kinerja keuangan perusahaan dilakukan menggunakan analisis ratio keuangan, dengan memanfaatkan data neraca dan laporan laba rugi perusahaan di tahun yang sama. Hasil analisis menunjukkan kinerja keuangan PT Unilever Indonesia, Tbk tahun 2021-2024 kurang baik di lihat dari ratio likuiditas, leverage, efisiensi, ratio profitabilitas dan ratio pasar. Kondisi ini menjadi penanda bagi manajemen untuk lebih memperhatikan produksi agar tidak berlebihan di gudang, juga strategi penjualan harus di manage kembali, sehingga laba yang dihasilkan bisa maksimal sekaligus menjadi magnet bagi investor baru untuk berinvestasi pada perusahaan. Perusahaan harus selektif menggunakan utang dan struktur finansial harus di perhatikan. Penting bagi manajemen perusahaan untuk memperhatikan kinerja keuangan perusahaan karena ini akan memberi gambaran kinerja perusahaan secara menyeluruh.